2015
DOI: 10.1038/ijo.2015.1
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal changes in bile acid levels and 12α-hydroxylation after Roux-en-Y gastric bypass surgery in type 2 diabetes

Abstract: INTRODUCTION Gastric bypass surgery (GBP) leads to sustained weight loss and significant improvement in type 2 diabetes (T2DM). Bile acids (BAs), signaling molecules which influence glucose metabolism, are a potential mediator for the improvement in T2DM after GBP. This study sought to investigate the effect of GBP on BA levels and composition in individuals with T2DM. METHODS Plasma BA levels and composition and fibroblast growth factor (FGF)-19 levels were measured during fasting and in response to an oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 68 publications
(107 reference statements)
6
65
2
Order By: Relevance
“…Most short-term studies (< 2 months after surgery) report unchanged or decreased levels of total BAs [26][27][28], while most studies reporting data from several months and years after surgery report increased concentrations [18,20,[29][30][31][32]. Our findings are in accordance with the existent literature, and extend the current knowledge by showing that the BA levels apparently continue to increase up to 5 years after RYGB.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Most short-term studies (< 2 months after surgery) report unchanged or decreased levels of total BAs [26][27][28], while most studies reporting data from several months and years after surgery report increased concentrations [18,20,[29][30][31][32]. Our findings are in accordance with the existent literature, and extend the current knowledge by showing that the BA levels apparently continue to increase up to 5 years after RYGB.…”
Section: Discussionsupporting
confidence: 83%
“…A study of patients with type 2 diabetes observed, contrary to their hypothesis, an increase in this ratio after RYGB [28]. Our study, which mostly included nondiabetic subjects, also demonstrated an increased ratio after both procedures at 5 years.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The authors concluded that the bile acids did not explain the rapid improvement in glucose and lipid metabolism or the stimulation of GLP-1. Temporal changes in bile acids and 12a-hydroxylation after Roux en Y operations have been recently reported by Dutia et al [43] They found that fasting bile acids were generally reduced at 1 month, but increased after 2 years, whereas postprandial bile acids were unchanged at 1 month, but there was an exaggerated peak at 2 years. The ratio of 12a-hydroxylated bile acids to non 12a bile acids was increased at 2 years, but not at 1 month, again suggesting that an early improvement in glucose metabolism is unrelated to the changes in bile acids.…”
Section: Effect Of Bile Acids On Lipid and Glucose Metabolismmentioning
confidence: 95%